Wait Times for Diagnostic Colonoscopy among Outpatients with Colorectal Cancer: A Comparison with Canadian Association of Gastroenterology Targets - Michael Sai Lai Sey; Jamie Gregor; Paul Adams; Nitin Khanna; Chris Vinden; David Driman; Nilesh Chande (Canadian Journal of Gastroenterology)
BACKGROUND: Timely access to colonoscopy is a nationally recognized issue in Canada, with previous studies documenting significant wait times for a variety of indications. However, specific wait times for colonoscopy among patients diagnosed with colorectal cancer remain unknown.